Pemberdayaan Masyarakat Di Desa Kalikurmo Berbasis Kearifan Lokal - Yohanes Martono; Maria Endah Retno Palupi; Betsy Felita; Sekar Nurani Saptaningtyas; Bereka Meidelivia Raharjianti; Fransiskus Tri Wahyu Hananto (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2020)
This community service activity is aimed at empowering the people of Kalkurmo Village, Beringin District, Semarang Regency through the processing of local natural resources. The appropriate technology being trained is the processing of corn into modified flour which can then be processed into various processed food products. Activities carried out in the form of training and community assistance to master post-harvest corn processing technology. Corn has been successfully processed into flour by fermentation and acetylation and then made into cookies. Cookies products can be used as processed food products to be marketed.